1980
DOI: 10.1113/jphysiol.1980.sp013509
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the rod network in the tiger salamander retina mediated by membrane properties of individual rods

Abstract: SUMMARY1. The spread of electrical signals between rods in the salamander retina was examined by passing current into one rod and recording the voltage responses in nearby rods. Rod network behaviour, measured in this way, was simulated from data on rod membrane properties gathered in voltage-clamp experiments on single isolated rods.2. The network voltage responses to square current pulses became smaller, more transient, and had a longer time-to-peak, for rods further away from the site of current injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
175
1
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(194 citation statements)
references
References 35 publications
16
175
1
2
Order By: Relevance
“…As signals spread through the rod network they become more transient, suggesting that response acceleration in individual rods is important in network function (Attwell and Wilson, 1980). Detwiler et al (1978) found that the voltage response to a bar of light peaked earlier in rods farther away from the bar.…”
Section: Roles For I Kx In the Rod Response To Lightmentioning
confidence: 99%
See 2 more Smart Citations
“…As signals spread through the rod network they become more transient, suggesting that response acceleration in individual rods is important in network function (Attwell and Wilson, 1980). Detwiler et al (1978) found that the voltage response to a bar of light peaked earlier in rods farther away from the bar.…”
Section: Roles For I Kx In the Rod Response To Lightmentioning
confidence: 99%
“…Since this voltage waveform is unchanged by Cs + (Fain et al, 1978;Owen and Torre, 1983), there has been speculation that currents other than I h shape small signals (Fain et al, 1978;Werblin, 1979;Attwell and Wilson, 1980;Fain and Lisman, 1981;Owen andTorre, 1981, 1983;Baylor et al, 1984). These may be K + currents because the "negative conduction velocity" of small transient signals propagating in the rod network, which is mediated by voltage-gated ion channels (Detwiler et al, 1978;Attwell and Wilson, 1980), is inhibited by high external K + concentrations (Owen and Torre, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical coupling between rod photoreceptors has been extensively explored using both experimental and modeling approaches (Copenhagen and Owen, 1976;Lamb and Simon, 1976;Schwartz, 1976;Detwiler et al, 1978;Werblin, 1978;Attwell and Wilson, 1980;Attwell et al, 1984;Tessier-Lavigne and Attwell, 1988;Hornstein et al, 2005;Zhang and Wu, 2005;Li et al, 2012). Coupling shapes the rod network properties and the light response of each rod (Attwell and Wilson, 1980;Attwell et al, 1984;Tessier-Lavigne and Attwell, 1988;Hornstein et al, 2005;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Coupling shapes the rod network properties and the light response of each rod (Attwell and Wilson, 1980;Attwell et al, 1984;Tessier-Lavigne and Attwell, 1988;Hornstein et al, 2005;Li et al, 2012). Estimates of the rod junctional conductance, a direct measure of the rod-rod coupling strength, range between 0 and Ͼ600 pS (Zhang and Wu, 2005;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%